2023
DOI: 10.18502/ijps.v19i1.14347
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dialectical Behavior Therapy in the Treatment of Borderline Personality Disorder: A Systematic Review of Randomized Controlled Trials

Milton Hernandez-Bustamante,
Julio Cjuno,
Ronald M. Hernández
et al.

Abstract: Objective: Borderline personality disorder (BPD) is a serious public health problem. Dialectical Behavior Therapy (DBT) is a program that has provided encouraging results for its treatment. However, scientific evidence about its efficacy is scarce. Therefore, we aimed to describe the scientific production on the components of the DBT program and its therapeutic efficacy in the treatment of people with BPD. Method: A systematic review with relevant keywords was conducted based on studies available in Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…DBT draws upon principles from behavioral and cognitivebehavioral psychotherapy, dialectical philosophy, and Zen practices [26]. The systematic reviews conducted in 2006, 2010, 2021, and 2024 [26][27][28][29] support the effectiveness of DBT for patients with BPD regarding self-injurious behaviors, depression, and suicidality. Both individual and group DBT promote the development of psychosocial and motivational skills that help foster adaptive and functional behaviors [30].…”
Section: Introductionmentioning
confidence: 99%
“…DBT draws upon principles from behavioral and cognitivebehavioral psychotherapy, dialectical philosophy, and Zen practices [26]. The systematic reviews conducted in 2006, 2010, 2021, and 2024 [26][27][28][29] support the effectiveness of DBT for patients with BPD regarding self-injurious behaviors, depression, and suicidality. Both individual and group DBT promote the development of psychosocial and motivational skills that help foster adaptive and functional behaviors [30].…”
Section: Introductionmentioning
confidence: 99%
“…Research has confirmed the effectiveness of some evidence-based psychotherapies such as dialectical behavior therapy (DBT; Hernandez-Bustamante et al, 2023) and schema-focused therapy (SFT; Zhang et al, 2023) in treating patients with BPD. Transference-focused psychotherapy (TFP) is another effective therapy for treating people with BPD.…”
mentioning
confidence: 99%